ANALISIS KOMPETENSI SDM DALAM PENGGUNAAN ALAT DIGITALISASI ADMINISTRASI KEPOLISIAN (AK) 23 DI KEPOLISIAN NEGARA REPUBLIK INDONESIA - Rusdiana, Agung; Asropi, Asropi; Silitonga, Mala Sondang (Jurnal Academia Praja, 2024)
The purpose of this study is to identify the factors that influence the competence of human resources (HR) in the use of the Police Administration Digitalization tool (AK) 23 and to formulate strategies to improve HR competence. The researcher analyzes the factors affecting HR from 8 factors, namely Beliefs and Values, Experience, Skills, Personality Characteristics, Intellectual Ability, Motivation, Emotional Issues, and Organizational Culture. This research uses a qualitative method with a scope in the Pusinafis Bareskrim Polri and Regional Identification. The research analysis technique used is descriptive analysis. The results of research from 8 factors found 1 factor that most influences, namely Organizational Culture. From these problems, the researcher offers strategies that can be used to improve HR competence which in the end can increase the achievement of fingerprint data input. The results of this study are expected to be used as a reference and material for preparing the next Pusinafis strategic plan (Renstra) in 2025 to 2029. And most importantly, the need for commitment and concern from the Police leadership to overcome the problems of Regional Identification.